2022
DOI: 10.3389/fphys.2021.815758
|View full text |Cite
|
Sign up to set email alerts
|

Novel Targets and Interventions for Cognitive Complications of Diabetes

Abstract: Diabetes and cognitive dysfunction, ranging from mild cognitive impairment to dementia, often coexist in individuals over 65 years of age. Vascular contributions to cognitive impairment/dementia (VCID) are the second leading cause of dementias under the umbrella of Alzheimer’s disease and related dementias (ADRD). Over half of dementia patients have VCID either as a single pathology or a mixed dementia with AD. While the prevalence of type 2 diabetes in individuals with dementia can be as high as 39% and diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 146 publications
(224 reference statements)
0
1
0
1
Order By: Relevance
“…Interestingly, decreased SUA was observed in diabetic patients with DPN. Similarly, a previous study showed lower SUA in T2DM patients with mild cognitive impairment than those without cognition decline [41], which is a kind of dysfunction in the central nervous system [42,43]. To confirm the occurrence of DPN, the conduction velocity of nerve was compared.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, decreased SUA was observed in diabetic patients with DPN. Similarly, a previous study showed lower SUA in T2DM patients with mild cognitive impairment than those without cognition decline [41], which is a kind of dysfunction in the central nervous system [42,43]. To confirm the occurrence of DPN, the conduction velocity of nerve was compared.…”
Section: Discussionmentioning
confidence: 94%
“…Микрососудистые осложнения включают диабетическую ретинопатию, нефропатию, невропатию, энцефалопатию и др. [14,15,17,18], к макрососудистым в первую очередь относят атеросклеротические изменения в сосудах сердца и головного мозга (ГМ) [9,14,15].…”
Section: Introductionunclassified